Penerapan Sistem Informasi Bimbingan Belajar Siswa Kelas XII Berbasis Web Pada SMA Negeri 1 Wewewa Utara - Noknisius B. Dola; Stefanus D.I.Mau; Sihang Gregorius Bali Mema (GLOBAL SCIENTS PUBLISHER, 2026)
Tutoring is an important service in education that aims to help students overcome learning difficulties and improve academic achievement. However, at SMA Negeri 1 Wewewa Utara, tutoring activities are still carried out manually, from recording to reporting, which results in low efficiency and limited access to information for students. This problem encourages the development of a web-based tutoring information system that can support the tutoring process more effectively and documented. This study aims to design and build a web-based student tutoring information system that can be used by tutors and students. The system was developed using the Waterfall method, which consists of the stages of needs analysis, system design, implementation, testing, and maintenance. The technology used in this system includes the Code Igniter 4 programming language as a database, and HTML and CSS for the user interface. The results of this study indicate that the developed information system is able to facilitate the recording of tutoring activities, scheduling consultation sessions, and reporting student progress in a digital and structured manner. With this system, the tutoring process becomes more efficient and easily accessible to students and teachers at any time via the internet. This system is also expected to be the initial foundation for the development of other information systems at SMA Negeri 1 Wewewa Utara in order to support the digital transformation of education.